Rosmarinic Acid as Potential Anti-Inflammatory Agent - Colica, Carmela; Di Renzo, Laura; Aiello, Vincenzo; De Lorenzo, Antonino; Abenavoli, Ludovico (Reviews on Recent Clinical Trials, 2018)
Rosmarinus officinalis L. (Lamiaceae), popularly known as rosemary, is used for food flavoring, and in folk medicine, as an antispasmodic, analgesic, anti-rheumatic, diuretic, and antiepileptic agent. Rosemary is an herb widely used in folk medicine, cosmetics, and phytotherapy and for flavoring of food products. Studies have focused on various biological activities of the secondary metabolites of this plant, such as rosmarinic acid, which have powerful antioxidant, hepato-protective, antimicrobial, anti-nociceptive, and anti-inflammatory properties.
Keywords: cytokines